2018
DOI: 10.3390/agronomy8050069
|View full text |Cite
|
Sign up to set email alerts
|

Resource Use Efficiencies of C3 and C4 Cereals under Split Nitrogen Regimes

Abstract: Abstract:Resources are limited, thus improving resource use efficiency is a key objective for cereal-based cropping systems. This field study was carried out to quantify resource use efficiencies in selected C 3 and C 4 cereals under split nitrogen (N) application regimes. The study included the following treatments: six cereals (three C 3 : wheat, oat, and barley; and three C 4 : maize, millet, and sorghum) and four split N application regimes (NS 1 = full amount of N at sowing; NS 2 = half N at sowing + half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 47 publications
0
6
0
3
Order By: Relevance
“…Narayanan (2007) concluded that sorghum loses its physiological activity under water scarcity during the vegetative phase (before flowering) without significantly reducing the yield. The water stress in the early stage of grain sorghum has a much greater inhibitory effect on grain yield than in other phases and stages (Abbas et al, 2020;Ahmad et al, 2012Ahmad et al, , 2015Fatima et al, 2018). After flowering, stress shortens the period of grain filling, which reduces the size and seed number and leads to reduced yield or even a complete crop failure (Mkhabela, 1995;Naz et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Narayanan (2007) concluded that sorghum loses its physiological activity under water scarcity during the vegetative phase (before flowering) without significantly reducing the yield. The water stress in the early stage of grain sorghum has a much greater inhibitory effect on grain yield than in other phases and stages (Abbas et al, 2020;Ahmad et al, 2012Ahmad et al, , 2015Fatima et al, 2018). After flowering, stress shortens the period of grain filling, which reduces the size and seed number and leads to reduced yield or even a complete crop failure (Mkhabela, 1995;Naz et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There are few published reports on the effect of sowing time on the phenology of sorghum varieties and grain yield under different irrigation conditions and different environments (Chapman et al, 2000;Fatima et al, 2018Fatima et al, , 2020Shahzad and Ahmad, 2019;Koláčková et al, 2020). Therefore, this research focused on evaluating the response of sorghum cultivars to different irrigation regimes and planting dates under the agroecological conditions of semi-arid at Sahiwal and arid at Multan in Punjab province, Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Wilson et al (2018) demostraron que el mayor rendimiento para avena variedad Turquesa se obtuvo a los 112 días después de la siembra con 6 702 kg ha -1 en estado lechoso-masoso. Zartash et al 2018, reportaron aproximadamente 5 000 kg ha -1 a los 160 días después de la siembra. Se reportaron 6 074 kg ha -1 de rendimiento en grano de avena Chihuahua a los 164 días después de la emergencia en el ciclo verano-otoño (Hernández-Campuzano et al, 2018).…”
Section: Rendimiento De Materia Seca Radiación Interceptada Y Materiunclassified
“…Lo anterior, confirma que la mayor cantidad de biomasa se obtiene en etapas anteriores a la madurez fisiológica. En cereales de invierno, justamente antes de la antesis, se alcanza el mayor índice de área foliar (Zartash et al, 2018). Da Silva y Hernández-Garay (2010), reportaron que, en pastos tropicales y templados, el punto óptimo de cosecha se alcanza con una RI de 95 moles de fotones interceptados (100 moles de fotones incidentes) -1 .…”
Section: Rendimiento De Materia Seca Radiación Interceptada Y Materiunclassified
See 1 more Smart Citation